Hiệu quả tài chính doanh nghiệp dưới góc nhìn “kinh nghiệm vừa đủ của Giám đốc điều hành”: Bằng chứng thực nghiệm tại Việt Nam - Hà Phước , Vũ; Nguyễn Thị Thanh , Bình (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study employs Feasible Generalized Least Squares (FGLS) regression to examine the linear and nonlinear effects of CEO experience on the financial performance of non-financial firms listed on the Ho Chi Minh City Stock Exchange (HOSE) over the period 2013–2022. The findings indicate a negative relationship between CEO experience and financial performance, accompanied by an inverted U-shaped nonlinear pattern, whereby financial performance initially rises with increasing years of CEO experience, reaches a peak at approximately 10 years, and subsequently declines. Moreover, during the COVID-19 pandemic, prior accumulated executive experience does not significantly enhance financial performance, highlighting the limitations of traditional experience in adapting to unprecedented economic shocks.